First record of Trichoglossum velutipes (Geoglossaceae, Ascomycetes) for Mexico - Diaz-Barriga, Horalia (Instituto de Ecología, A.C., 1988)
As part of studies on the fungi of the State of Michigan, Mexico, in this paper Trichoglossum velutipes (Peck) Durand is reported for the first time for the Mexican mycoflora.